CILINAYA: NASKAH SASAK BERNUANSA ISLAM - R Aris Hidayat (Analisa: Journal of Social Science and Religion, 2008)
Currently there is an indication of crisis of self-identity/nationalidentity. This is remarked by blurred social solidarity, kinship, and social friendliness in line with reinforced materialism values. To restrenghten self-identity I national-identity, government and society tryto discover values in manuscripts. Manuscripts are past cultural treasures that full of noble values. This research aimed to discover and tore-actualize noble values in a manuscript as an improvement and strengthen model of social solidarity, kinship and social friendlinessvalues that tend to blur.This research examined a manuscript entitled Cilinaya. This manuscript is a Sasak's Islamic manuscript stored in West Nusa TenggaraMuseum. The aim of current research are to discover Islamic thoughtsin Sasak 's manuscript expected to contain noble values as a source ofimprovement and strengthening social solidarity, kinship and socialfriendliness that currently are blurring. The research used philologyapproach and content analysis with Roland Barthes' semioticpostructural method to discover cultural codes in this literature work.The results showed that (I) Cilinaya manuscript of such palm leavesis one of Sasak's syncretism Islamic literature works. It contents Islamic and Hinduism substances as well as local custom. (2) Islamicsubstances in Cilinaya manuscript are oneness and morals. Onenessrelated to oneness of God (Allah), while morals related to human beinginterrelationship. This moral aspect regulated moral ethics and behavioral rules in their society life. ( 3) Hinduism and custom aspects in this manuscript covered different human being classes based on caste andpresenting offerings to God and considered God as a point to askingand prayerful for help.